Annual Report on Exchange Arrangements and Exchange Restrictions 1954. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1954)
This paper discusses actions taken by members themselves, particularly for the establishment of internal financial stability, are of primary importance for the elimination of restrictions. The IMF has sought to give its support to countries faced with the practical difficulty of establishing such policies, pointing out the importance of appropriate exchange rate policies in achieving a sound international financial position and the importance of internal stability for exchange rate policy. Many member countries have now reached a point where they are re-examining more carefully not only their need for the current level of restrictions, but also the more fundamental question of reliance upon restrictions to cope with balance of payments difficulties. In the first year of IMF consultations, although some countries were applying policies designed to produce favorable conditions for the removal of restrictions, most countries were so preoccupied with their immediate problems that any substantial withdrawal of restrictions was impracticable.